2008
DOI: 10.1111/j.1530-0277.2008.00740.x
|View full text |Cite
|
Sign up to set email alerts
|

Hazardous Drinking: Prevalence and Associations in the Finnish General Population

Abstract: The high prevalence of hazardous drinking makes it an important public health concern. Hazardous drinkers have different sociodemographic characteristics as compared to people in other alcohol use categories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
28
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 25 publications
(38 reference statements)
6
28
0
Order By: Relevance
“…A study from Russia found that 75% of the men drank spirits [13], while a Thailand study which was done among subjects who were aged 12-65 years, showed the prevalence of current drinkers to be 28.6% [14]. A study which was done in Finland showed the prevalence of hazardous drinking to be 5.8% [15]. The difference which was observed in prevalence may be due to difference in the exposure status of associated risk factors in different geographical locations.…”
Section: Methodsmentioning
confidence: 96%
“…A study from Russia found that 75% of the men drank spirits [13], while a Thailand study which was done among subjects who were aged 12-65 years, showed the prevalence of current drinkers to be 28.6% [14]. A study which was done in Finland showed the prevalence of hazardous drinking to be 5.8% [15]. The difference which was observed in prevalence may be due to difference in the exposure status of associated risk factors in different geographical locations.…”
Section: Methodsmentioning
confidence: 96%
“…Smoking status was measured with a variable describing current regular smoking (current/never/ex-smoker). High alcohol intake was present with a weekly self-reported consumption of beer, wine, and spirits exceeding ≥175 g of alcohol for women and ≥263 g of alcohol for men 42. Survey reports on height and weight were used to calculate the average body mass index (BMI) to identify underweight (BMI<20 kg/m 2 ), normal-weight (BMI 20−<25 kg/m 2 ), overweight (25−<30 kg/m 2 ), and obese (BMI ≥30 kg/m 2 ) participants.…”
Section: Methodsmentioning
confidence: 99%
“…In another study the prevalence of heavy drinking was 11% among 30-to 65-year-olds [14]. Heavy drinking was more prevalent among males than females (17% vs. 5%) [14]. According to the WHO Alcohol Report 2004 in Sweden the rate of heavy drinking among drinkers was 4% among males and 3.3% among females in age group 20 to 64 years.…”
mentioning
confidence: 99%
“…Using the CAGE questionnaire the prevalence of heavy drinking in primary care and the general population was 20% and 16% among men and 9% and 13% among women [12]. In another study the prevalence of heavy drinking was 11% among 30-to 65-year-olds [14]. Heavy drinking was more prevalent among males than females (17% vs. 5%) [14].…”
mentioning
confidence: 99%